Moving from physical literacy to co-existing physical literacies: What is the problem?. (February 2023) - Young, Lisa; Alfrey, Laura; O'Connor, Justen
This paper explores how various ideological positions or 'cosmoses' associated with physical literacy (PL) have come to be and, in doing so, extends scholarship by examining and presenting PL as a multiplicity of physical literacies. Drawing on Stengers' notion of 'cosmopolitics' and Venturini's 'cartography of controversies' method, 167 scholarly articles and 23 non-scholarly texts were analysed to observe and describe how PL has been framed over time as a result of dynamic political factors. Findings reveal that three 'waves' of PL cosmoses have unfolded over time (PL as health-promoting physical activity, PL as motor competence and PL as phenomenological embodiment). Whilst all three seek to promote engagement in physical activity and have loose ties to 'health', each PL cosmos is bound by different objectives, actors and obligations and is orientated towards solving a different problem. Rather than continued confusion and controversy, we propose that PL be understood as a multiverse wherein the three different PL cosmoses are held apart as physical literacies that play co-existing roles based on the problem that each cosmos is trying to solve. While understanding PL as a multiverse is not a solution to the controversy and uncertainty surrounding PL, it provides those who are interested in or tasked with enacting PL an opportunity to become aware of and understand what the different PL cosmoses or physical literacies constitute and thus make possible (or not) on the basis of their ontological differences.